2020
DOI: 10.1017/s0007114520001063
|View full text |Cite
|
Sign up to set email alerts
|

Low hydration status may be associated with insulin resistance and fat distribution: analysis of the Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2010

Abstract: We aimed to identify the association of hydration status with insulin resistance (IR) and body fat distribution. A total of 14 344 adults participated in the Korea National Health and Nutrition Examination Survey 2008–2010. We used urine specific gravity (USG) to indicate hydration status, and HOMA-IR (homoeostasis model assessment of IR) and trunk:leg fat ratio (TLR) as primary outcomes. In multivariate logistic regression, the OR per 0·01 increase in USG for high IR was 1·303 (95 % CI 1·185, 1·433; P < 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(62 reference statements)
0
1
0
Order By: Relevance
“… 42 Data from the Korea National Health and Nutrition Examination Survey showed that low hydration status was linked to insulin resistance and changes in fat distribution. 43 These data highlight the interaction between the regulation of glucose and vasopressin signaling.…”
Section: Vasopressin and Metabolic Disease In Humansmentioning
confidence: 89%
“… 42 Data from the Korea National Health and Nutrition Examination Survey showed that low hydration status was linked to insulin resistance and changes in fat distribution. 43 These data highlight the interaction between the regulation of glucose and vasopressin signaling.…”
Section: Vasopressin and Metabolic Disease In Humansmentioning
confidence: 89%